2022
DOI: 10.1007/s00068-022-02153-0
|View full text |Cite
|
Sign up to set email alerts
|

Those who speak survive: the value of the verbal component of GCS in trauma

Abstract: Aim To evaluate the value of the individual components of GCS in predicting the survival of trauma patients in the Emergency Department. Methods Trauma patients who were admitted for more than 24 h or died after arrival at Al-Ain Hospital from January 2014 to December 2017 were studied. Children < 16 years, elderly > 80 years, patients with facial injuries, those intubated in the ER, and those with missing primary outcomes were excluded. Demography, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…In the present study, GCS verbal scores also played a significant role in the model. However, previous studies have shown conflicting results regarding the impact of GCS verbal scores on patient survival scores [ [31] , [32] , [33] ]. the main reason for the disagreement was whether the patient was extubated at the time of scoring, and if extubation had been performed, the GCS verbal score could not be accurately assessed [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, GCS verbal scores also played a significant role in the model. However, previous studies have shown conflicting results regarding the impact of GCS verbal scores on patient survival scores [ [31] , [32] , [33] ]. the main reason for the disagreement was whether the patient was extubated at the time of scoring, and if extubation had been performed, the GCS verbal score could not be accurately assessed [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…the main reason for the disagreement was whether the patient was extubated at the time of scoring, and if extubation had been performed, the GCS verbal score could not be accurately assessed [ 34 ]. Cevik et al believed that if a complete GCS score was successfully obtained, then the GCS verbal score could be a good predictor of patient survival [ 32 ]. To overcome the issue of inaccurate assessment of GCS verbal scores due to extubation, we conducted a comprehensive GCS evaluation at the time of patient admission, before tracheal intubation.…”
Section: Discussionmentioning
confidence: 99%